Training for the new millennium : pedagogies for translation and interpreting - Tennent, Martha (Benjamins translation library, 2005)
Originating at an international forum held at the University of Vic (Spain), the twelve essays collected here attest to important changes in translation practice and the assumptions which underpin them. Leading theorists respond to the state of Translation Studies today, particularly the epistemological dilemma between theories that are empirically oriented and those that are inspired by developments in Cultural Studies. But the volume is also practical. Experienced instructors survey existing pedagogies at translator/interpreter training programs and explore new techniques that address the te.